MORAL VALUES DEPICTED ON THE HELP MOVIE (2011) DIRECTED BY TATE TAYLOR - Dimyati, Farhan; Nurhapituddin, Irman (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2024)
This study discusses moral values depicted on The Help movie. The Help movie was chosen as an object is directed by Tate Taylor and released in 2011. This movie depicts moral values provide some massage for the viewer through narration and visual in the movie. The research method in this research uses literary criticism method and structural approach that are needed to obtain in-depth data and careful reading of the text, a data that contains meaning. To find out moral values and it types, this study uses one critical theory as the great theory of Utile et Dulce by Horace and the main theory of moral understanding by Frank Palmer. As a result of this research, the writer found three categories about moral values in this movie, the first is relationship between human beings and own self. In this form researcher got some of moral value in The Help movie as like discipline, courage, honesty, toughness, steadfatness, sacrificed, friendliness. The second is relationship between human beings and other. Researcher got some of moral value that include the second form, kind-hearted, caring, sympathetic to the other, cooperative, thankfulness, helpful, justice, and tolerance. Human do interaction each other to keep a good relationship. The last is relationship between human and God. Worship and prayers.Keyword: Moral values, human, The Help, movie.